Effects of glyphosate acid and the glyphosate-commercial formulation (Roundup) on Dimorphandra wilsonii seed germination: Interference of seed respiratory metabolism. (January 2017) - Gomes, Marcelo Pedrosa; da Silva Cruz, Fernanda Vieira; Bicalho, Elisa Monteze; Borges, Felipe Viègas; Fonseca, Marcia Bacelar; Juneau, Philippe; Garcia, Queila Souza
Abstract: Glyphosate-formulations are widely used in the Brazilian Cerrado (neotropical savanna) with little or no control, threatening population of the endangered species Dimorphandra wilsonii . We investigated the toxicity of different concentrations (0, 5, 25 and 50 mg l −1 ) of glyphosate acid and one of its formulations (Roundup ® ) on seed germination in D . wilsonii . Glyphosate acid and Roundup drastically decreased seed germination by decreasing seed respiration rates. The activation of antioxidant enzymes, ascorbate peroxidase and catalase assure no hydrogen peroxide accumulation in exposed seeds. Glyphosate acid and the Roundup-formulation negatively affected the activities of enzymes associated with the mitochondrial electron transport chain (ETC), with Complex III as its precise target. The toxicity of Roundup-formulation was greater than that of glyphosate acid due to its greater effects on respiration. The herbicide glyphosate must impair D . wilsonii seed germination by disrupting the mitochondrial ETC, resulting in decreased energy (ATP) production. Our results therefore indicate the importance of avoiding (or closely regulating) the use of glyphosate-based herbicides in natural Cerrado habitats of D . wilsonni as they are toxic to seed germination and therefore threaten conservation efforts. It will likewise be important to investigate the effects of glyphosate on the seeds of other species and to investigate the impacts of these pesticides elsewhere in the world. Graphical abstract: Highlights: Glyphosate and Roundup decreased Dimorphandra wilsonni seed germination. Both compounds impact the mitochondrial electron transport chain. Compounds affect energy generation necessary for seed germination. Herbicide use in natural habitats of should be avoided. Abstract : Glyphosate acid and its commercial formulation, Roundup, interfere with germination by affecting the respiration metabolism in exposed seeds.